Asesmen Computational Thinking di Pendidikan Matematika: Analisis Bibliometrik Menggunakan Vosviewer - Ria, Reny Refitaningsih Peby (EDUPEDIKA: Jurnal Studi Pendidikan dan Pembelajaran, 2023)
Computational Thinking (CT) is a thinking skill that is needed in mathematics education. CT-based mathematics education can train students to develop problem solving, analyze data, perform modeling, and train algorithmic thinking skills. This study aims to describe the visualization of bibliometric network mapping between keywords in CT assessment research in mathematics education and find recommendations for CT assessment topics in mathematics education that provide opportunities for future research. This type of research uses descriptive research with a bibliometric approach. The data collection technique used secondary data from the Scopus database. The data analysis technique uses bibliometric analysis with the help of VOSviewer software. The results of bibliometric analysis using VOSviewer found in the visualization network there are 5 cluster themes. While in the results of overlay visualization and density visualization, CT research shows that for the topics of assessment, instrument, mathematics, education there has not been much research done so there are opportunities for research by taking or collaborating these topics.